Endozoochoric dispersal of plants in oak forest at Tlaxcala by ringtail cat (Bassariscus astutus) - Pérez-Flores, Guillermo Alejandro; Sánchez-Sánchez, Monserrat; Sánchez-Alarcón, Juana; García-de Jesús, Sandra; Flores-Morales, Minerva (Ecosistemas y Recursos Agropecuarios, 2022)
Seed dispersal is an ecological process that causes effects on plant communities structure to maintenance of their diversity. The passage of seeds through the digestive tract of some vertebrates has evident effects on germination, the mammal Bassariscus astutus includes fruits in its omnivorous diet, this has been documented in various ecosystems, and has a marked tolerance to disturbance. With aim to evaluate the effects of the dispersal of four plant species by B.astutus, feces found in latrines were located, collected and processed. Seeds were recovered, identified and subjected to viability and germination tests, in addition, germination and establishment in latrines were quantified. Seeds of plants Juniperus deppeana, Phytolacca icosandra, Opuntia depressa and Amelanchier denticulata were found in 76 feces from 35 latrines. The results showed positive effects of dispersion on O. depressa and J. deppeana with a higher percentage of viability and germination when they came from endozoocoria, without effects on P. icosandra and A. denticulata. In the latrines, only J. deppeana and O. depressa appear to be benefited by endozoocoria and the site conditions. The effect of dispersal by B. astutus on the germination and recruitment of plants from a temperate forest was evidenced; it is important to consider maintenance of this process at the site.